2018
DOI: 10.1007/s00464-018-6187-z
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive esophagectomy attenuates the postoperative inflammatory response and improves survival compared with open esophagectomy in patients with esophageal cancer: a propensity score matched analysis

Abstract: MIE significantly attenuated postoperative serum CRP levels compared with OE. MIE could contribute to improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Except for the differences in approach to lymphanectomy of the left and right approaches, the surgical incision itself may affect the survival. With the same extent of lymphanectomy, another retrospective study has demonstrated that the MIE could achieve lower operative morbidity and long time survival benefits (12). The survival benefits may due to the different incisions.…”
Section: Figure 1 | Kaplan-meier Curves For Comparison Of Overall Surmentioning
confidence: 99%
“…Except for the differences in approach to lymphanectomy of the left and right approaches, the surgical incision itself may affect the survival. With the same extent of lymphanectomy, another retrospective study has demonstrated that the MIE could achieve lower operative morbidity and long time survival benefits (12). The survival benefits may due to the different incisions.…”
Section: Figure 1 | Kaplan-meier Curves For Comparison Of Overall Surmentioning
confidence: 99%
“…Based on the short‐term and long‐term results of the TIME trial, they concluded that MIE is useful for treating esophageal cancer . Yamashita et al compared short‐term and long‐term outcomes between 121 OE and 121 MIE using propensity score matching. All MIE consisted of TEP.…”
Section: Minimally Invasive Esophagectomy Versus Open Esophagectomymentioning
confidence: 99%
“…DFS and OS rates were significantly better in the MIE group than in the OE group (3‐year DFS rate, 81.7% vs 69.3%; log‐rank P = 0.021; 3‐year OS rate, 89.9% vs 79.2%; log‐rank P = 0.007) (Table ). The authors concluded that MIE is an independent prognostic factor for patients with esophageal cancer . Takeuchi et al compared short‐term outcomes between MIE, including both TELD and TEP, and OE using a nationwide database in Japan.…”
Section: Minimally Invasive Esophagectomy Versus Open Esophagectomymentioning
confidence: 99%
“…[ 24 ] Due to some high quality studies were published recently, we can take this advantage to conduct a systematic review and meta-analysis with higher level of evidences. [ 25 29 ] Moreover, in order to minimize the heterogeneity and bias, we will select randomized controlled trials (RCTs) and propensity score matched comparative studies which matched across a range of baseline factors to generate 2 similar groups for comparison. If data are sufficient, we will also conduct subgroup analyses in different surgical procedures of MIE.…”
Section: Introductionmentioning
confidence: 99%